2013
DOI: 10.1080/15475441.2013.753798
|View full text |Cite
|
Sign up to set email alerts
|

Harder Words: Learning Abstract Verbs with Opaque Syntax

Abstract: Highly abstract predicates (e.g. think) present a number of difficulties for language learners (Gleitman et al., 2005). A partial solution to learning these verbs is that learners exploit regularities in the syntactic frames in which these verbs occur. While agreeing with this general approach to learning verbs, we caution that this strategy is not sufficient for learning another class of abstract verbs known as "raising" verbs (seem) since their argument structure frames cannot always be directly read off of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Second, animacy for each NP argument was annotated by hand. We included animacy because a number of acquisition studies have demonstrated that animacy is a useful cue for learning verb classes (Scott & Fisher, 2009;Becker, 2009;Kirby, 2009aKirby, , 2010Becker & Estigarribia, 2013;Becker, 2014Becker, , 2015Hartshorne et al, 2015). Third, thematic roles for the arguments of each verb (except the copula be) were annotated by hand using 13 thematic role labels that are common in the literature (again, see the readme file mentioned above for details).…”
Section: The Input-intake Pathway 421 Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, animacy for each NP argument was annotated by hand. We included animacy because a number of acquisition studies have demonstrated that animacy is a useful cue for learning verb classes (Scott & Fisher, 2009;Becker, 2009;Kirby, 2009aKirby, , 2010Becker & Estigarribia, 2013;Becker, 2014Becker, , 2015Hartshorne et al, 2015). Third, thematic roles for the arguments of each verb (except the copula be) were annotated by hand using 13 thematic role labels that are common in the literature (again, see the readme file mentioned above for details).…”
Section: The Input-intake Pathway 421 Inputmentioning
confidence: 99%
“…Animacy is something young children are known to both be sensitive to as a general property and also use as a cue in experimental studies to predict how verbs will behave (Scott & Fisher, 2009;Becker, 2009;Kirby, 2009aKirby, , 2010Becker, 2014Becker, , 2015Hartshorne et al, 2015). Moreover, if children are able to harness animacy effectively in their input, it's possible to use the animacy of a verb's arguments (in particular, whether the argument is inanimate) to distinguish verb behaviors such as those associated with subject-raising, subject-control, objectraising, and object-control (Kirby, 2009a(Kirby, , 2010Becker & Estigarribia, 2013;Becker, 2014). One way to implement this conceptual information is for the verb's NP arguments to be labeled as +/-animate, as in (6b).…”
Section: Linguistic Intakementioning
confidence: 99%
“…Children are then asked to point to, or their eye gaze is tracked toward a visual image depicting the relevant action (Fisher, 2002; Hirsh-Pasek & Golinkoff, 1996; Naigles, 1990; Yuan & Fisher, 2009). The methodology has been adapted to test learners’ interpretations of not only verbs denoting observable actions but also relatively more abstract kinds of verbs, such as those that could have a meaning like think or seem , or to abstract adjectives such as easy (Becker, 2006, 2014, 2015; Becker & Estigarribia, 2013; Papafragou, Cassidy, & Gleitman, 2007). In some cases, such as for abstract verbs such as think , the sentence frame is even more informative than extragrammatical situational context (what is going on in the world when a particular verb is uttered) for cueing children to the predicate’s meaning (Gleitman et al, 2005; Papafragou et al, 2007).…”
Section: The Role Of Linguistic Cues In Word Learningmentioning
confidence: 99%
“…Evidence for the bias to map animate or agentive NPs to the most prominent syntactic position comes not only from psycholinguistic studies with children and adults (Clark & Begun 1971, Trueswell & Tanenhaus 1994, Mak et al 2002, Traxler et al 2005, Becker 2005, Becker & Estigarribia 2013, but also from argument hierarchies in language that are based on broad typological patterns. Well-known hierarchies such as the Animacy Hierarchy (Silverstein 1976, Dixon 1979) and the Thematic Hierarchy (Jackendoff 1972), as well as the Promotion to Subject Hierarchy (Keenan 1976) show how widespread the preference is in human language to associate animacy and agency with syntactic prominence, and inanimacy with lower positions.…”
Section: Displacementmentioning
confidence: 99%
“…In my previous work I have argued that hearing an inanimate subject in sentences like (1) and ( 2) can provide such a trigger by signaling that the subject and main predicate are not thematically related (i.e. not in an argument structure relationship), and therefore that the subject is displaced from elsewhere in the sentence (Becker 2005, 2006, 2014, 2015, Mitchener & Becker 2011, Becker & Estigarribia 2013. Inanimate subjects provide a helpful clue because inanimate NPs cannot be agents or experiencers and therefore can't be the subject argument of a control predicate (the ones found in (3) and ( 4)).…”
Section: Inanimate Subjects As Cues To Structurementioning
confidence: 99%